177k views
10 votes
Simplify, y-8(y+12) + 4

NEED HELP​

User Sschilli
by
5.5k points

2 Answers

4 votes
so first distribute the 8 out then add everything together:

y-8y-96+4 = -7y-92
User Vikkyhacks
by
4.6k points
9 votes


\huge\text{Hey there!}


\huge\textbf{Equation:}


\mathbf{y - 8(y + 12) + 4}


\huge\textbf{Solving:}


\mathbf{y - 8(y + 12) + 4}

\huge\textbf{DISTRIBUTE -8 WITHIN the}\\\\\\\huge\textbf{PARENTHESES:}


\mathbf{= y - 8(y) - 8(12) + 4}


\mathbf{= y - 8y - 96 + 4}


\huge\textbf{COMBINE the LIKE TERMS:}


\mathbf{= (y - 8y) + (-96 + 4)}


\mathbf{= y - 8y - 96 + 4}


\huge\textbf{Simplify it!}


\mathbf{ = -7y - 92}


\huge\textbf{Answer:}


\huge\boxed{\mathbf{ -7y - 92}}\huge\checkmark


\huge\text{Good luck on your assignment \& enjoy your day!}

~
\frak{Amphitrite1040:)}

User Farooq Ahmed Khan
by
5.1k points